Important Flavonoids and Their Role as a Therapeutic Agent - Ullah, Asad; Munir, Sidra; Badshah, Syed Lal; Khan, Noreen; Ghani, Lubna; Poulson, Benjamin Gabriel; Emwas, Abdul-Hamid; Jaremko, Mariusz (Molecules (Basel, Switzerland), 2020)
Flavonoids are phytochemical compounds present in many plants, fruits, vegetables, and leaves, with potential applications in medicinal chemistry. Flavonoids possess a number of medicinal benefits, including anticancer, antioxidant, anti-inflammatory, and antiviral properties. They also have neuroprotective and cardio-protective effects. These biological activities depend upon the type of flavonoid, its (possible) mode of action, and its bioavailability. These cost-effective medicinal components have significant biological activities, and their effectiveness has been proved for a variety of diseases. The most recent work is focused on their isolation, synthesis of their analogs, and their effects on human health using a variety of techniques and animal models. Thousands of flavonoids have been successfully isolated, and this number increases steadily. We have therefore made an effort to summarize the isolated flavonoids with useful activities in order to gain a better understanding of their effects on human health.